The Perceived Influence of Social Media Usage on Job Performance: Insights from Public Sector Employees - Olasupo, Idrees Olanrewaju; Okunlola , John Olayemi; Adedayo, Oni Lawrence (Journal of Governance Risk Management Compliance and Sustainability, 2025)
The study explored the perceived influence of social media usage on job performance among civil servants in the Oyo State Secretariat, Ibadan, Nigeria. As social media increasingly permeates professional environments, its dual effects, positive and negative, have become subjects of interest. The research adopts a descriptive survey design, drawing a sample of 350 civil servants from 10 ministries, departments, and agencies within the Secretariat. Data were collected using a validated questionnaire and analysed through descriptive statistics and Pearson's Moment Correlation Coefficient. The findings revealed that the prevalent personal use of social media during work hours negatively influences job performance. Findings indicate that social media platforms, particularly WhatsApp, Facebook, and Instagram, are widely used by civil servants for personal communication and, to a lesser extent, for professional purposes such as work-related discussions and information retrieval. The study highlighted a statistically significant negative correlation between the intensity and frequency of social media usage and job performance (r = -0.254, p < 0.05). While social media facilitates networking, real-time communication, and problem-solving, excessive use during productive hours leads to distractions and reduced efficiency. The study, therefore, concluded that social media usage needs structured guidelines and recommends policies to balance its benefits and drawbacks. Training and awareness initiatives are also advised to enhance their professional utility while minimising disruptions. This research offers critical insights for policymakers aiming to optimize workforce productivity in public sector settings.